Veterinary Compounding: Regulation, Challenges, and Resources - Gigi Davidson (Pharmaceutics, 2017)
The spectrum of therapeutic need in veterinary medicine is large, and the availability of approved drug products for all veterinary species and indications is relatively small. For this reason, extemporaneous preparation, or compounding, of drugs is commonly employed to provide veterinary medical therapies. The scope of veterinary compounding is broad and focused primarily on meeting the therapeutic needs of companion animals and not food-producing animals in order to avoid human exposure to drug residues. As beneficial as compounded medical therapies may be to animal patients, these therapies are not without risks, and serious adverse events may occur from poor quality compounds or excipients that are uniquely toxic when administered to a given species. Other challenges in extemporaneous compounding for animals include significant regulatory variation across the global veterinary community, a relative lack of validated compounding formulas for use in animals, and poor adherence by compounders to established compounding standards. The information presented in this article is intended to provide an overview of the current landscape of compounding for animals; a discussion on associated benefits, risks, and challenges; and resources to aid compounders in preparing animal compounds of the highest possible quality.